First-principles calculations to investigate the structural, electronic and optical properties of lead-free double perovskites Rb2SeI6 and K2SeI6. (1st January 2022) - Hu, De-Yuan; Zhao, Xian-Hao; Tang, Tian-Yu; Lu, Li-Min; Li, Li; Gao, Li-Ke; Tang, Yan-Lin
Highlights: The band gap values of Rb2 SeI6 and K2 SeI6 are 1.51 eV and 1.45 eV, respectively, which are very suitable for use as photosensitive materials of solar cells. The optical parameters indicate that Rb2 SeI6 and K2 SeI6 have better light absorption characteristics than most lead-free perovskite materials, especially in the visible light range. The effective mass of electrons and holes of Rb2 SeI6 and K2 SeI6 are much small than that of many perovskite materials. Abstract: In this work, we have studied in detail the structural, electronic and optical properties of lead-free double perovskites Rb2 SeI6 and K2 SeI6 based on first-principles calculations. Their negative binding energy (Eb ) and formation energy (Ef ) ensure the stability of the studied materials. Our calculations give band gap values of Rb2 SeI6 and K2 SeI6 to be 1.51 eV and 1.45 eV, respectively. This illustrates that the two perovskite compounds belong to indirect band gap semiconductors, and are suitable for photosensitive materials of solar cells. For both Rb2 SeI6 and K2 SeI6, the valence band maximum (VBM) are dominated by the I-p orbitals, and their conduction band minimum (CBM) are mainly contributed from the I-p orbitals and the Se-p orbitals. The results indicate that the effective mass of electrons and holes in Rb2 SeI6 and K2 SeI6 is very small, and therefore they are favorable for carrier transport. Moreover, the optical parameters display that Rb2 SeI6 and K2 SeI6 have significant light absorption properties, especially in the visible light range. Due to the suitable band gap values and excellent light absorption, Rb2 SeI6 and K2 SeI6 have great application potential in the absorption layer of solar cells.